THE EFFECT OF ORGANIZATION’S STRUCTURE AND TASK CHARACTERISTICS ON TEAM EFFECTIVENESS IN TUBERCULOSIS PREVENTION PROGRAM - Sinta Dewi Lestyoningrum; Thinni Nurul Rochmah; Dewi Retno Suminar; Ulfia Hazna Safira (Indonesian Journal of Health Administration, 2020)
Background: A team is a vital element for an organization. An organization should put efforts to improve team performance even though they might face some obstacles. Organization’s structure and task characteristics resulted in different team effectiveness of primary healthcare centres in preventing tuberculosis (TB) cases in Surabaya.Aims: This study aimed to identify the effect of organization’s structure and task characteristics on team effectiveness of primary healthcare centers in TB prevention program in Surabaya.Methods: The reasearch was a quantitative study using a cross-sectional approach. Questionnaires were disseminated to 43 respondents as the samples selected with a proportional stratified random sampling technique based on the success rate. The respondents consisted of doctors, nurses, and health analysts who were directly involved in the Tuberculosis prevention program. This study used a linear multivariable regression test to confirm the most significant model for the independent variable.Results: The span of control and centralization had a significant effect on task characteristics (sig 0.00; sig 0.017). The dimensions of task characteristics that had a significant effect on team effectiveness were task variety, task identity, and task significance.Conclusion: There was a significant effect of span of control and centralization on task characteristics. The primary healthcare centers should provide access to technology to upgrade the span of control and centralization and their understanding of task characteristics. Keywords: health services, organization’s structure, task characteristics, team effectiveness, tuberculosis.